The Poetry of Mary Robinson - Robinson, D. author. aut Link
XI, 287 p.
Keywords: Once celebrated as 'the English Sappho,' Mary Robinson was a major figure in British Romanticism. This volume offers comprehensive study of Robinson's achievement as a poet, a professional writer, a formative influence on the Romantic movement, and a participant in the literary, political, and social scene of the late 1700s.